Police and state crime in the Americas: southern and postcolonial perspectives - Gascón, Daniel; Sclofsky, Sebastián; Perez, Xavier; Sanabria, Jhon; Mejia Mesinas, Analicia (Palgrave's Critical Policing Studies, 2024)
Imperial Regimes -- Chapter 1: Uruguayan Police in the Age of Conservative Hegemony by Rafael Paternain -- Chapter 2: Securing Citizens, Pacifying Subjects and Criminalizing “Others”: The Dark Side of Community Policing in Latin America by Markus-Michael Müller -- Chapter 3: Tribal Law and Order and the Settler-Colonial Logics of Reservation Policing by Theresa Rocha Beardall -- Colonial Organizations -- Chapter 4: Policing Immigrant Communities: An Assessment of State Sanctioned Violence in the Name of Migration Control by Mercedes Valadez and Jennifer Noble -- Chapter 5: Techniques and Technologies: The Military Expansion of São Paulo’s Municipal Civil Guard by José Douglas dos Santos Silva -- Chapter 6: Policing in Puerto Rico: Reforms of the Twenty First Century, by Xavier Perez and Jhon Sanabria -- Repressive Encounters -- Chapter 7: Nos Quedamos Marcados: The Carceral Regime’s Ripple Effect on Mexican Families by Marlene Mercado -- Chapter 8: How Black Genocide Happens: Military Patronage, Policing, and the Coloniality of Gender in Rio de Janeiro Favelas by Carla dos Santos Mattos -- Chapter 9: The Criminology of State Violence will include interviews with critical theorists, Biko Agozino and Guillermina Seri -- Chapter 10: Counter-Colonial Methods includes interviews with critical methodologists, Robert Duran and Nicolas Barrera -- Chapter 11: Between Accountability and Alternatives is an interview with police reformers, Jhon Sanabria and Bernardo Gill.